1999
DOI: 10.1021/om9806693
|View full text |Cite
|
Sign up to set email alerts
|

1,2-eq,eq-[Re2(CO)8(THF)2]:  A Reactive Re2(CO)8Fragment That Easily Activates H−H and C−H Bonds

Abstract: The reaction of [Re2(μ-H)2(CO)8] (1) with diazomethane at 193 K in THF-d 8 gives the unstable [Re2(μ-H)(μ-CH3)(CO)8] derivative (2) containing a methyl group arising from the insertion of CH2 into a Re−H−Re bond. Isotopic perturbation of the equilibria by partial deuteration demonstrated that the methyl bridges the Re−Re bond in an unsymmetrical way, with a fast exchange between one agostic and two terminal C−H bonds. At temperatures higher than 253 K, 2 decomposes, in THF solution, with CH4 elimination to giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 60 publications
1
20
0
3
Order By: Relevance
“…Finally In conclusion, this work and our previous investigation 16 have shown that by using silanolate ligands which better mimic the chemistry and topology of the silica surface it is reasonable to hypothesize that the first step of the interaction of [Re 2 (CO) 10 ] with the silica surface involves a [Re 2 (CO) 8 was prepared by following a reported procedure 23 and was usually contaminated with unreactive [Re 3 (µ-H) 3 (CO) 12 ] (ca. 10%), which could be easily removed after the reaction.…”
Section: Resultsmentioning
confidence: 63%
“…Finally In conclusion, this work and our previous investigation 16 have shown that by using silanolate ligands which better mimic the chemistry and topology of the silica surface it is reasonable to hypothesize that the first step of the interaction of [Re 2 (CO) 10 ] with the silica surface involves a [Re 2 (CO) 8 was prepared by following a reported procedure 23 and was usually contaminated with unreactive [Re 3 (µ-H) 3 (CO) 12 ] (ca. 10%), which could be easily removed after the reaction.…”
Section: Resultsmentioning
confidence: 63%
“…Seminal studies on this subject have been performed on tri-and tetra-osmium clusters by Deeming et al [16], Shapley et al 10 , under UV irradiation [19], and on Re 2 (CO) 8 (THF) 2 [20]. As a result, cluster compounds containing g 2 -bound olefins are rather uncommon [21], and are usually stable at low temperature and in the presence of excess olefin [22].…”
mentioning
confidence: 99%
“…[Re 6 (m-H) 5 (CO) 24 ] À : der erste Carbonylcluster mit einer cyclohexanartigen Struktur** Mirka Bergamo, Tiziana Beringhelli, Giuseppe DAlfonso,* Pierluigi Mercandelli, Massimo Moret* und Angelo Sironi Vor kurzem haben wir die Synthese des fünfkernigen ringförmigen Clusters [Re 5 (m-H) 4 (CO) 20 ] À beschrieben; [1] wir erhielten diesen durch die Cycloaddition des [Re 3 H 2 -(m-H) 2 (CO) 12 ] À -Anions und des Re 2 (CO) 8 -Fragments, das sich aus dem labilen Komplex [Re 2 (CO) 8 (thf) 2 ] [2] bildet (Schema 1). Die Reaktion beruht auf der wohlbekannten s-Donor-Fähigkeit von M-H-Bindungen gegenüber koordinativ Schema 1.…”
unclassified
“…Dies könnte der Grund dafür sein, daû die zu 3 führende Cycloaddition weniger selektiv ist als die zum Re 5 -Ring führende Reaktion. [19] Experimentelles [Re 2 (m-H) 2 Neuartige ternäre Alkalimetallsilberacetylide M I AgC 2 (M I Li, Na, K, Rb, Cs)** Winfried Kockelmann und Uwe Ruschewitz* Vor kurzem konnten wir zeigen, daû durch Umsetzung von Na 2 C 2 mit Palladium oder Platin bei Temperaturen um 350 8C in einer Inertgasatmosphäre Na 2 PdC 2 und Na 2 PtC 2 hergestellt werden können. [1] Diese Verbindungen sind die ersten ternären Alkalimetallübergangsmetallacetylide.…”
unclassified
See 1 more Smart Citation